2023
DOI: 10.1002/ece3.9672
|View full text |Cite
|
Sign up to set email alerts
|

The global depth range of marine fishes and their genetic coverage for environmental DNA metabarcoding

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 129 publications
(146 reference statements)
0
3
0
Order By: Relevance
“…Arguably, any detected effect of lacking reference data may have been less pronounced by using another, or multiple primer pairs. For example, some studies suggest that the MiFish primer set provides poor taxonomic resolution and a low success rate in species recovery (Jackman et al, 2021), especially for endemic species (Duhamet et al, 2023) while other studies highlight its usefulness in ecosystem conservation strategies, enhanced taxonomic resolution, and efficient fish biodiversity monitoring (Miya et al, 2015;Schroeter et al, 2020;Zhu & Iwasaki, 2023). Furthermore, our primer evaluations with the more recently released software GAPeDNA (Marques et al, 2021) (released after our experiments were completed) show that, for example, the "Fish 16S" primer set (McInnes et al, 2017) would have covered 249 instead of the 119 New Zealand marine fish species covered by our MiFish 12S data (Table S1).…”
Section: Osmeriformesmentioning
confidence: 99%
“…Arguably, any detected effect of lacking reference data may have been less pronounced by using another, or multiple primer pairs. For example, some studies suggest that the MiFish primer set provides poor taxonomic resolution and a low success rate in species recovery (Jackman et al, 2021), especially for endemic species (Duhamet et al, 2023) while other studies highlight its usefulness in ecosystem conservation strategies, enhanced taxonomic resolution, and efficient fish biodiversity monitoring (Miya et al, 2015;Schroeter et al, 2020;Zhu & Iwasaki, 2023). Furthermore, our primer evaluations with the more recently released software GAPeDNA (Marques et al, 2021) (released after our experiments were completed) show that, for example, the "Fish 16S" primer set (McInnes et al, 2017) would have covered 249 instead of the 119 New Zealand marine fish species covered by our MiFish 12S data (Table S1).…”
Section: Osmeriformesmentioning
confidence: 99%
“…Meanwhile, it worked out and successfully discriminated some fish species in other sites (Figure 5). A study has also showed that Teleo primer covered fewer species than MiFish-U could (Duhamet et al 2023). Despite more orders and families detected using MiFish-U primer, a note remains in which Teleo primer could complement the MiFish-U.…”
Section: Comparison Between Mifish-u and Teleo Primermentioning
confidence: 99%
“…The evaluation of five primer pairs for eDNA metabarcoding of Central European fish species based on mock communities discovered differences in primer efficiency depending on the species and primer preferential species in different fish (Macher et al 2023). Furthermore, the genetic coverage of both primers by depth and ocean was assessed, highlighting potential differences in their performance (Duhamet et al 2023). Using different primer pairs can lead to variations in amplification efficiency, taxonomic coverage, and preferential species, potentially contributing to inconsistencies in eDNA analysis results.…”
Section: Comparison Between Mifish-u and Teleo Primermentioning
confidence: 99%
“…Metabarcoding analyses require barcode libraries consisting of reference barcode sequences originating from specimens that have been previously identified for taxonomic assignment of the eDNA sequences (Duhamet et al, 2023). However, reference libraries are incomplete and may potentially contain sequences from specimens that have been misidentified (Lindsay et al, 2017;Bucklin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%